Forum 63 - Van de Walle, A.L.J.; Geirlandt, K.J.; de Vree, Paul (Ledeberg : Erasmus, 1963)
Van Anderlecht, Englebert ; Arman ; Assar, Nasser ; Beekman, Jan ; Benrath, Frédéric ; Bluhm, Norman ; Bogaert, André ; Bogart, Bram ; van Bohemen, Kees ; Van Breedam, Camiel ; De Buck, Walter ; Burssens, Jan ; Bury, Pol ; César ; Christo ; D'Haese, Roel ; D'Havé, Camille ; Damian, Horia ; Deschamps, Gérard ; Dierickx, Karel ; Dionyse, Carmen ; Domoto, Hisao ; Dries, Jan ; Dufrêne, François ; Dyckmans, Bruno ; Falkenstein, Claire ; Ficheroux, Mathieu ; Fievre, Yolande ; Foldes, Peter ; Ganzevoort, Wybrand ; Geissler, Klaus ; Gentils, Vic ; Van Gijsegem, Paul ; Golub, Leon ; Hains, Raymond ; Hiltmann, Jochen ; Van Hoeydonck, Paul ; Kemeny, Zoltan ; Klein, Yves ; Landuyt, Octave ; Lardera, Berto ; Lataster, Ger ; Leblanc, Walter ; de Leeuw, Bert ; Lerin, Fernando ; Loth, Wilhelm ; Lucas, Richard ; Mack, Heinz ; Mara, Pol ; Martini, Remo ; Mees, Guy ; Metcalf, James ; Millares, Manolo ; Monteyne, Roland ; Motz, Wim ; Noël, Georges ; Ossorio, Alfonso ; Peire, Luc ; Piene, Otto ; Raveel, Roger ; Recalcati, Antonio ; Romijn, Gust ; Rotella, Mimmo ; de Saint-Phalle, Niki ; Saul, Peter ; Saura, Antonio ; Scanavino, Emilio ; Schoonhoven, Jan ; Van Severen, Dan ; Soto, Jesus Rafael ; Spoerri, Daniel ; Swimberghe, Gilbert ; Tàpies, Antoni ; Theys, Yvan ; Ting, Walasse ; Tinguely, Jean ; Uecker, Günther ; Ung No Lee ; Vandenbranden, Guy ; Vanderheyden, Jaak ; Vercammen, Wout ; Verheyen, Jef ; Verstockt, Mark ; Vilain, Walter ; Villeglé, Jacques ; Vlerick, Pierre ; De Vogelaere, Fons (Alfons) ; Wagemaker, Jaap ; Wittevrongel, Roger ; Ysewijn, Marcel
Vermelding P. Vlerick nr.119
Forum '63, Centrum voor Kunstambachten gewezen St.-Pietersabdij, Gent, 01.06 - 04.08.1963
Schenking Pierre Vlerick
kunstcatalogus